Institutional bases and international assessment of the ecological component of sustainable development - Batava, Nadezhda N. (Journal of the Belarusian State University. Ecology, 2018)
The institutional environmental effect on sustainable development as well as contradictions between its environmental, social and economic components are revealed. It is established that cultural traditions, religion, institutes property greatly impact the choice of environmental and economical policy, and determine individual formation of systainable type of development in each country when maintaining its general principles.
Keywords: sustainable development; ecology; sotsio-ekologo-economic relations; economic growth; «green» growth; ecological indicators